Thymineless Death in Escherichia coli: Strain Specificity - Cummings, Donald J. (1967)
Thymineless death of various ultraviolet (UV)-sensitive strains of Escherichia coli B and K-12 was investigated. It was found that E. coli B, B(s−12), K-12 rec-21, and possibly K-12 Lon(−), all sensitive to UV, were also sensitive to thymine starvation. However, other UV-sensitive strains of E. coli were found to display the typical resistant-type kinetics of thymineless death. The correlation of these results with various other cellular processes suggested that the filament-forming ability of the bacteria might be involved in the mechanism of thymineless death. It was apparent from the present results that capacity for host-cell reactivation, recombination ability, thymine dimer excision, and probably induction of a defective prophage had little to do with determining sensitivity to thymine deprivation.